giải pt: √(12-3/x²) + √(4x²-3/x²) = 4x²

Question

giải pt: √(12-3/x²) + √(4x²-3/x²) = 4x²

in progress 0
Rose 2 tháng 2021-07-18T20:19:06+00:00 2 Answers 1 views 0

Answers ( )

    0
    2021-07-18T20:20:36+00:00

    Điều kiện xác định và điều kiện có nghiệm:

    $x^2\ge \dfrac{3}{4}, x\ne 0$

    Đặt $a = \sqrt {12 – \dfrac{3}{{{x^2}}}} ,b = \sqrt {4{x^2} – \dfrac{3}{{{x^2}}}}$

    $\begin{array}{l} a = \sqrt {12 – \dfrac{3}{{{x^2}}}} ,b = \sqrt {4{x^2} – \dfrac{3}{{{x^2}}}} \\  \Rightarrow a + b = 4{x^2}\left( 1 \right)\\  \Rightarrow {a^2} – {b^2} = 12 – 4{x^2}\left( 2 \right)\\ \left( 1 \right) \to \left( 2 \right) \Rightarrow \left( {a – b} \right) = \dfrac{{12 – 4{x^2}}}{{4{x^2}}} = \dfrac{3}{{{x^2}}} – 1\left( 3 \right)\\ \left( 1 \right) – \left( 3 \right) \Rightarrow 2b = 4{x^2} – \dfrac{3}{{{x^2}}} +1 = {b^2} + 1\\  \Rightarrow {\left( {b – 1} \right)^2} = 0\\  \Leftrightarrow b = 1 \Leftrightarrow \sqrt {4{x^2} – \dfrac{3}{{{x^2}}}}  = 1\\  \Leftrightarrow 4{x^2} – \dfrac{3}{{{x^2}}} = 1\\  \Leftrightarrow 4{x^4} – {x^2} – 3 = 0\\  \Leftrightarrow \left( {{x^2} – 1} \right)\left( {4{x^2} + 3} \right) = 0\\  \Leftrightarrow {x^2} = 1 \Leftrightarrow x = \pm 1 \Rightarrow x =\pm1 \\  \Rightarrow S = \left\{ \pm 1 \right\} \end{array}$

    0
    2021-07-18T20:21:05+00:00

    Đáp án: $x = ± 1$

     

    Giải thích các bước giải:

    ĐKXĐ$: x \neq 0$

    $ 12 – \dfrac{3}{x²} ≥ 0 ⇔ x² ≥ \dfrac{1}{4} ⇔ x ≤ – \dfrac{1}{2}; x ≥ \dfrac{1}{2}$

    $ 4x² – \dfrac{3}{x²} ≥ 0 ⇔ x^{4} ≥ \dfrac{3}{4} ⇔ x ≤ – \sqrt[4]{\dfrac{3}{4}}; x ≥ \sqrt[4]{\dfrac{3}{4}}$

    Kết hợp lại $x ≤ – \sqrt[4]{\dfrac{3}{4}}; x ≥ \sqrt[4]{\dfrac{3}{4}}$

    $ PT ⇔ \sqrt{4x² – \dfrac{3}{x²}} + sqrt{12 – \dfrac{3}{x²}} = 4x² (1)$

    $ ⇔ (4x² – \dfrac{3}{x²}) – (12 – \dfrac{3}{x²}) = 4x²(\sqrt{4x² – \dfrac{3}{x²}} – sqrt{12 – \dfrac{3}{x²}})$

    $ ⇔ \sqrt{4x² – \dfrac{3}{x²}} – \sqrt{12 – \dfrac{3}{x²}} = 1 – \dfrac{3}{x²} (1)$

    $(1) + (2) $ vế với vế:

    $ 2\sqrt{4x² – \dfrac{3}{x²}} = 4x² – \dfrac{3}{x²} + 1$

    $ ⇔ (\sqrt{4x² – \dfrac{3}{x²}} – 1)² = 0 ⇔ \sqrt{4x² – \dfrac{3}{x²}} = 1$

    $ ⇔ 4x² – \dfrac{3}{x²} = 1 ⇔ 4x^{4} – x² – 3 = 0$

    $ ⇔ (x² – 1)(4x² + 3) = 0$

    $ ⇔ x² – 1 = 0 ⇔ x² = 1 ⇔ x = ± 1 (TM)$

     

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )